POTRET PROSES PEMBELAJARAN FISIKA KELAS X SMA DI KABUPATEN SIKKA - Wea, Kristiana Nathalia; Elizabeth, Agustina; Mole, Paulina (PendIPA Journal of Science Education, 2025)
This study aims to analyze the physics learning process in grade X of senior high schools in Sikka Regency, focusing on learning approaches, student engagement, as well as supporting and inhibiting factors during the learning activities. The research employed a descriptive non-experimental method using observation techniques in eight schools, with an instrument in the form of an observation sheet that had been tested for content validity. Data were analyzed through the stages of reduction, presentation, and conclusion drawing. The findings revealed that the aspect of the role of physics in education scored 77%, the learning approach aspect 78%, and the aspect of handling students with diverse abilities 67%. Teachers have been fairly effective in fostering logical and critical thinking, as well as creating active and contextual learning interactions. However, the implementation of inclusive learning, the use of technology for differentiation, and assessment variety still need improvement. This study recommends strengthening differentiated learning strategies, implementing diagnostic assessments, and utilizing interactive media such as Genially to enhance the quality and inclusiveness of physics learning.